The evolving project of labour law : foundations, development and future research directions - Howe, John; Chapman, Anna; Landau, Ingrid (Annandale, N.S.W. : Federation Press, 2017)
This collection draws together contributions from leading Australian and international labour law scholars, based on papers delivered at a conference to mark the 21st birthday of the Centre for Employment and Labour Relations Law at the University of Melbourne. Collectively, the contributions provide an account and exploration of labour law scholarship's evolution over the last two decades, and its future trajectory. They explore a number of enduring and emerging themes in labour law. The book offers conclusions about the progress that labour law scholarship has made in facing fundamental changes in the organisation of capital, work and labour markets, as well as suggesting ideas for how labour law might continue to evolve to meet new challenges.
1. The evolving project of labour law in Australia / John Howe, Anna Chapman and Ingrid Landau -- 2. The evolution of the idea of a labour law subject in Australian legal scholarship / Richard Mitchell -- 3. Updating the labour market regulation perspective on labour law / C J Arup -- 4. When was'labour law'? / Anthony O'Donnell -- 5. A different world : the regulatory project in labour law / John Howe -- 6. Evaluating the adverse action provisions of the Fair Work Act : equality thwarted? / Beth Gaze, Anna Chapman and Adrianna Orifici -- 7. At the intersection of education and work : young people, equality and regulation of the labour market / Anne Hewitt, Rosemary Owens, Andrew Stewart and Joanna Howe -- 8. Normative visions of age : progress and change in Australian labour law / Alysia Blackham -- 9. Regulating health and safety in'vertically disintegrated' work arrangements : the example of supply chains / Richard Johnstone -- 10. Watch this space : mapping the actors involved in the implementation of labour standards regulation in Australia / Tess Hardy -- 11. Researching labour law'in practice' : challenges in assessing the impact of protected industrial action ballot procedures on enterprise bargaining processes / Catrina Denvir and Shae McCrystal -- 12. Sidestepping labour law through the corporate form / Helen Anderson -- 13.'Predatory princes','migration merchants' or'agents of development'? An examination of the legal regulation of labour hire migration intermediaries / Joanna Howe -- 14. Agency work and its regulatory challenges : lessons learnt through a comparative overview of Australian and Italian approaches / Maria Azzurra Tranfaglia -- 15. Understanding Australian labour law discourse as international / Jill Murray -- 16. Using a historical institutionalist approach to assess the Cambodian better factories project / Shelley Marshall -- 17. Trade agreements and Australian labour law -- implications of the death of the Trans-Pacific Partnership Agreement / Joo-Cheong Tham and K D Ewing -- 18. Game changer? Human rights due diligence and corporate respect for workers' rights in a global economy / Ingrid Landau -- 19. Technology, the digital economy and the challenge for labour market regulation / Peter Gahan, Joshua Healy and Daniel Nicholson.
Includes bibliographical references and index.
Keywords: Labor laws and legislation -- Research -- Australia